Numerical study on fire resistance for fiber reinforced polymer reinforced concrete (FRP RC) under hydrocarbon fire / \c Nurul Izham bin M Shukeri - Nurul Izham M Shukeri (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2018)
The main objective is to study the fire resistance of FRP RC structural elements under HC fire at elevated temperatures. In order to achieve this main objective, the following sub-objectives will be performed ; to discretize 1D heat transfer equation on the direction of concrete thickness by using explicit finite difference method (EFDM) ; to construct computational algorithm of FDM heat transfer model and procedure for solving 1D heat transfer equation ; to validate the numerical result with NEFCOM experimental results ; to predict the temperature of FRP RC structure exposed with hydrocarbon fire.